The mechanism of tea tree oil regulating the damage of hydrogen sulfide to spleen and intestine of chicken - Yachao Wang; Yilei Liang; Yan Huang; Wei wang; Xiaoyan Long; Li Jiang; Tingting Cheng; Jinfeng Du; Xuegang Luo (Poultry Science)
Intensification of poultry industry has led to a surge in animal product output, but this has also revealed issues with environmental management in poultry houses, particularly the harmful effects of high hydrogen sulfide (H2S) levels on poultry health. The study aimed to assess the therapeutic impact of tea tree oil (TTO) on H2S-induced spleen and intestinal injuries in chickens. A total of 240 one-day-old Lohmann Brown chicks were randomly divided into three groups: the control group (CON), the H2S exposure group (AVG), and the TTO treatment group (TTG), with four replicates, each consisting of 20 chicks. The experiment lasted 42 days. Results showed that TTO treatment alleviated tissue damage in the thymus, kidneys, spleen, and bursa of Fabricius, and improved the organ index (P < 0.05) compared with the AVG. Serum analysis revealed that TTO lowered levels of alanine aminotransferase(ALT), aspartate aminotransferase(AST), triglycerides(TG), CD3 positive CD4 positive T cells(CD3+CD4+), CD4 positive to CD8 positive Rratio(CD4+/CD8+), and alkaline phosphatase(AKP), while increasing albumin(ALB), globulin(GLO), immunoglobulin A(IgA), and immunoglobulin G(IgG) levels (P < 0.05). Intestinal findings indicated that TTO treatment enhanced villus height, reduced crypt depth, and upregulated the expression of Claudin 1, Occludin, and ZO-1 mRNA in the jejunum (P < 0.05). After TTO treatment, H2S-induced oxidative stress injury and apoptosis protein expression in spleen were improved (P < 0.05). TTO also reduced interferon-γ(INF-γ), tumor necrosis factor-α(TNF-α) and interleukin-1β(IL-1β) proteins (P < 0.05), while raising CD3+CD8+ T-cell subsets (P < 0.05). Compared with CON, TTO treatment alleviated serum biochemical disorders and intestinal damage caused by H2S exposure and restored them to normal (P > 0.05). In conclusion, TTO can improve spleen and intestinal function and reduce the effects of H2S on growth performance and health of chickens.